Knowledge Regarding Osteoporosis among Young Adult Women of a Selected Community of Pokhara, Kaski (International Journal of Nursing Education, 2021)
Background: Osteoporosis is a silent killer disease that is highly prevalent among females. Even though thesymptoms of osteoporosis can be identified in later stages of life, it can be prevented with a healthy lifestyleadaptation at an early stage of life.Objectives: The present study aims to assess the knowledge level of osteoporosis among young adultfemales and examine the association between knowledge level and selected socio-demographic variables.Methodology: A quantitative descriptive cross-sectional study design was used. A non-probability purposivesampling technique was used to select 153 samples. The data were collected for 6 weeks using a semistructuredinterview schedule. Osteoporosis Knowledge assessment tool (OKAT) was used to collect thedata. Descriptive statistics (frequency, percentage, mean, standard deviation) was used for quantitative dataanalysis and inferential statistics (chi-square) were used to find out the association between knowledge leveland selected socio-demographic characteristics of the respondents.Results: The study concluded that 51 percent of the young adult women had an average level of knowledgeand 49 percent had a poor level of knowledge regarding osteoporosis. However, none of them had a goodlevel of knowledge regarding osteoporosis. A significant association was found between the knowledge leveland educational status of the respondents (p=0.002).
Keywords: Knowledge, osteoporosis, young adult women